Therapeutic characteristics of patients followed for bipolar disorder with rapid cycles: Study on a Tunisian population - M. Karoui; G. Amri; R. Kammoun; H. Nefzi; F. Ellouz (European Psychiatry, 2022)
Introduction Bipolar disorder is a frequent and particularly severe psychiatric pathology that causes significant morbidity and mortality. The rapid cycling forms are more severe in terms of their expression, evolutionary course, therapeutic responses and associated comorbidities.